STRATEGI DAN TANTANGAN PELESTARIAN MANUSKRIP DI PERPUSTAKAAN RUMOH MANUSKRIP ACEH - Nurul Rahmi; Nataca Aprida (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
Preservation is a process or way of protection and damage. This research was conducted at the Aceh Manuscript Rumoh Library (PRMA). This study aims to determine the strategies and challenges of preserving manuscripts in the Aceh manuscript house library. The research method used is descriptive qualitative research. Data collection techniques used by observation, interviews, and documentation. Researchers conducted interviews with one librarian who manages PRMA. The results of the study found that the preservation was carried out by PRMA by carrying out physical preservation and content preservation. Preservation of manuscripts is carried out by carrying out maintenance, conservation and restoration. Damage to manuscripts is caused by damage factors such as biological factors, physical factors, chemical factors, humans, and natural disasters. The strategy undertaken by PRMA is to continue to improve room cleanliness, provide equipment, facilities, and also attend seminars or training for library managers. The challenge for PRMA in carrying out conservation is the constraints on facilities, tools, and materials. Not all librarians are experts at preserving, so libraries need to recruit employees who are capable of preserving it so that the treasures can be enjoyed and used for a long time. Digitalization or media transfer is also a challenge for libraries. By transferring media, the information contained in the manuscript can be used and the value of the information is maintained.